The structure of English educational e-course within Moodle - A. O. Tomilina; M. V. Maloivan (Academy of Cognitive and Natural Sciences, 2014)
Research goal: to involve IT in the process of teaching English. Research objectives: to make up an English educational e-course for second-year students within Moodle. Object of research: the process of English teaching of students. Subject of research: the ways of using educational e-course within Moodle while English teaching. Research methods used: the study of the methodological materials of the chosen subject; didactic modeling; pedagogical prediction to monitor the effectiveness of the method used in teaching English. Results of the research. Electronic course of discipline provides high intensity of learning process of English based on Moodle. Learning English at the electronic course provides participants educational democratization of communication space and expands the range of foreign language communication. The main conclusions: this course has a complete structure and it focuses on students' gradual mastering of knowledge, abilities and skills the subject requires and systemic control and self-control.